Influence Of Outpatient Registration Services On Satisfaction Of Patient In General Hospital Fl. Tobing City Of Sibolga 2020 - Benri Situmorang (Institute of Computer Science (IOCS), 2021)
Quality health services are health services that can satisfy every service user in accordance with the level of satisfaction of the average population and its implementation in accordance with the standards of the professional code of ethics that have been set. However, enhancing patient satisfaction in low-income settings is very challenging due to the inadequacy of resources as well as low health literacy among patients [1]. This study aims to determine the effect of outpatient registration services on patient satisfaction at the General Hospital F.L Tobing Sibolga City. This type of research is quantitative descriptive research. The population in this study were all outpatients who came for treatment at the time of the study, the number of patients seeking treatment per day was 450 people at the F.L.Tobing Hospital, Sibolga City in 2020 and a sample of 45 people. Methods of data analysis by means of univariate analysis and bivariate analysis.